Studies on the antioxidant activity of some chromonylrhodanine derivatives. (6th November 2014) - Kruk, Irena; Piechowska, Teresa; Berczyński, Paweł; Kładna, Aleksandra; Bozdağ‐Dündar, Oya; Ceylan‐Unlusoy, Meltem; Aboul‐Enein, Hassan Y.
Abstract Fifteen chromonylrhodamine derivatives (CRs) were synthesized and the antioxidant activity levels were evaluated for the first time. The antioxidant activity potencies of these chromone derivatives were evaluated towards superoxide anion radicals, hydroxyl radicals and 2, 2‐diphenyl‐1‐picrylhydrazyl radicals. Also, the total antioxidant capacity of the tested compounds was measured using the ferric‐ferrozine assay. The antioxidant activities were investigated using a chemiluminescence (CL) assay, spectrophotometry measurements, direct electron paramagnetic resonance (EPR) and the EPR spin‐trapping technique. The 5, 5‐dimethyl‐ 1‐pyrroline‐1‐oxide (DMPO) was applied as spin trap. Eleven of the 15 chromone compounds exhibited a decrease in the CL accompanying the superoxide anion radical produced in anhydrous dimethylsulfoxide (DMSO), ranging from 71–94% at concentration of 1 mmol /L; four of these compounds enhanced light emission in the range 231–672%. Similarly, these compounds caused 28–58% inhibition in the intensity of the DMPO‐OOH radical EPR signal and the DMPO‐OH radical (from 12–48%). Furthermore, three of these compounds showed very good antioxidant response towards the DPPH radical (EC50: 0.51–0.56 µmol/L) and the high reduction potentials. These findings demonstrate that the chromone compounds tested may be considered as effective free radicals scavengers, a finding that is of great pharmacological importance. Copyright © 2014 John Wiley & Sons, Ltd.